Factors associated with severe sepsis or septic shock in complicated pyelonephritis. Issue 43 (October 2017) - Ruiz-Mesa, Juan D.; Marquez-Gomez, Ignacio; Sena, Gabriel; Buonaiuto, Veronica A.; Mora-Ordoñez, Juan; Salido, Manuel; Plata Ciézar, Antonio; Valiente-De Santis, Lucía.; Mediavilla, Concepción; Colmenero, Juan D.
Abstract : Abstract: Severe sepsis or septic shock are the main factors influencing the prognosis of acute pyelonephritis (APN). Our aim was to analyze factors associated with the development of severe sepsis or septic shock in a large sample of patients with acute complicated pyelonephritis (ACPN). This prospective observational study comprised 1507 consecutive patients aged 14 years or older who were admitted to a tertiary care hospital because of ACPN between 1997 and 2015. Covariates associated in univariate analysis with severe sepsis or septic shock were then analyzed by multivariate logistic regression. Of the 1507 patients, 423 (28.1%) fulfilled the criteria for severe sepsis or septic shock at the time of admission. Crude and attributable mortality at 30 days were 17.7% and 11.7% in patients with severe sepsis or septic shock versus 1.7% and 0.6% in patients without severe sepsis or septic shock, P < .0001 and P < .0005, respectively. An age > 65 years, urinary instrumentation in the previous 2 weeks, the lack of mictional syndrome or costovertebral tenderness, an ectasia ≥ grade II, and bacteremia were independent risk factors associated with severe sepsis or septic shock. The prevalence of severe sepsis and septic shock in patients with ACPN is high. Some factors associated with severe sepsis are easy to identify in any emergency department. The information provided here could be useful when deciding which patients should be admitted to receive immediate treatment.